Natural regeneration and early development of Scots pine seedlings after gap cutting in northern Finland - Miettinen, Janne; Hallikainen, Ville; Valkonen, Sauli; Hökkä, Hannu; Hyppönen, Mikko; Rautio, Pasi (Scandinavian Journal of Forest Research)
In the northern boreal region, tree growth, timber yields and economic returns are low, meaning low regeneration costs are the basis of profitable forestry. If natural regeneration is successful, it may be favoured over expensive planting or seeding. We studied the regeneration success and early growth of Scots pine in gaps in terms of seedling density and height 10 years after gap cuttings in central Finnish Lapland. Three gap sizes (diameters of 20, 40, and 80 m) were studied on patch scarified xeric and sub-xeric sites in six random blocks and a total of 18 replicates of each. The number of pine seedlings was high across the gap sizes. The proportion of empty regeneration plots (size 5 m2) was ∼ 2%. Site preparation substantially increased the number of seedlings. The growth of seedlings was faster in larger gaps, but a high proportion of exposed mineral soil decreased it. The results suggest that all studied gap sizes regenerated naturally well, and that soil scarification exposing 10–20% of the surface area or even less can be enough to achieve regeneration goals. Gaps of a diameter of 40 m or more are required to achieve an optimal balance between seedling density and growth. 2024